2013
DOI: 10.1111/tbed.12038
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Pseudorabies Virus Strains Isolated in Italy

Abstract: In this study, we undertook the genomic characterization of 54 pseudorabies virus (PRV) strains isolated in Italy during 1984-2010. The characterization was based on partial sequencing of the UL44 (gC) and US8 (gE) genes; 44 strains (38 for gene gE and 36 for gC) were isolated on pig farms; 9 originated from dogs and 1 from cattle. These porcine PRV strains, which were closely related to those isolated in Europe and America in the last 20 years, and the bovine strain bovine/It/2441/1992 belong to cluster B in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 14 publications
(23 reference statements)
1
37
0
Order By: Relevance
“…Sequences alignment and phylogenetic analysis of PRV isolates, showed that many protein-coding sequences of the TJ strain are identical or highly homologous to those of the BJ/YT strain, a PRV isolated from a dog in Beijing in 2012. PRV infections in dogs, because of hunting feral or domestic swine, have been reported (Cramer et al, 2011;Sozzi et al, 2014). The BJ/YT strain is closely related to recent Chinese PRV isolates of swine origin and thus likely to originate from pigs.…”
Section: Discussionmentioning
confidence: 96%
“…Sequences alignment and phylogenetic analysis of PRV isolates, showed that many protein-coding sequences of the TJ strain are identical or highly homologous to those of the BJ/YT strain, a PRV isolated from a dog in Beijing in 2012. PRV infections in dogs, because of hunting feral or domestic swine, have been reported (Cramer et al, 2011;Sozzi et al, 2014). The BJ/YT strain is closely related to recent Chinese PRV isolates of swine origin and thus likely to originate from pigs.…”
Section: Discussionmentioning
confidence: 96%
“…The mean coverage of the obtained consensus sequence representing the whole genome of ADV32751/Italy2014 (142,276 bp) was 841×. Previous studies demonstrated that the Italian SHV-1 strains are divided into three clusters (4) and that clear genetic distinction between strains isolated from hunting dogs exposed to wild boars and those originated from working dogs, with domestic pigs as likely sources, does exist (5). By phylogenetic analysis of partial gC gene sequences, ADV32751/Italy2014 apparently belongs to the Italian cluster 1 with other SHV-1 strains isolated from wild boars and hunting dogs in Italy (4).…”
Section: Genome Announcementmentioning
confidence: 99%
“…215 partial Ul44 nucleotide sequences of SuHV-1 were collected from GenBank with the largest possible amount of information available on host, year, and country of isolation [4,5,6,8,17,18,19,20,21,22,23]. The sequences were identified using the name of the isolate in GenBank followed by a three-letter code to identify the country of origin: Germany (GER), Argentina (ARG), Austria (AUS), Brazil (BRA), China (CHI), Croatia (CRO), Greece (GRE), South Korea (SKO), Slovakia (SLK), Spain (ESP), United States (USA), Japan (JAP), Hungary (HUN), Italy (ITA), Northern Ireland (NIR), Malaysia (MAL), or Sweden (SWE).…”
Section: Methodsmentioning
confidence: 99%